2020
DOI: 10.31971/16401808.48.1.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Different types of parental leave use by German fathers and their engagement in childcare in subsequent years

Abstract: This paper examines the relationship between different aspects of the parental leave use by German fathers and their subsequent engagement in childcare. The relationship between the use of parental leave by fathers and their time spent on childcare on weekdays in subsequent years is broken down by three different details to parental leave use (duration, timing and partner's employment status during parental leave). It also examines whether fathers who take parental leave provide more childcare even before they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…The changes effected through concrete policies are thus seen to have an impact on agents' behaviour, causing structural transformations that can modify social inertias and expectations. These results are consistent with the studies that have examined this issue in other countries (Huerta et al, 2014;Knoester et al, 2019;Reimer & Pfau-Effinger, 2020;Tamm, 2018), and they confirm our second hypothesis. The fathers who were not eligible for paternity leave at the birth of a child (generally fathers unemployed at the time) are not more involved in childcare than other fathers, because, while the coefficient is positive, it is not statistically significant.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The changes effected through concrete policies are thus seen to have an impact on agents' behaviour, causing structural transformations that can modify social inertias and expectations. These results are consistent with the studies that have examined this issue in other countries (Huerta et al, 2014;Knoester et al, 2019;Reimer & Pfau-Effinger, 2020;Tamm, 2018), and they confirm our second hypothesis. The fathers who were not eligible for paternity leave at the birth of a child (generally fathers unemployed at the time) are not more involved in childcare than other fathers, because, while the coefficient is positive, it is not statistically significant.…”
Section: Resultssupporting
confidence: 93%
“…The changes effected through concrete policies are thus seen to have an impact on agents’ behaviour, causing structural transformations that can modify social inertias and expectations. These results are consistent with the studies that have examined this issue in other countries (Huerta et al, 2014; Knoester et al, 2019; Reimer & Pfau-Effinger, 2020; Tamm, 2018), and they confirm our second hypothesis.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It seems, however, that to enhance gender equality between the spouses and change the traditional patterns of care, fathers' individual leave needs to last longer than just a week or two (Almqvist & Duvander, 2014;Bünning 2015;Everttson et al 2018;Hosking et al 2010;Miller 2011;Reimer & Pfau-Effinger 2020). For example, Bünning (2015), in her study based on German household panel data, argues that fathers who take simultaneous leave with their partners are likely to remain their child's secondary caregiver and mothers' assistant, whereas fathers on individual leave must learn to take full responsibility for both childcare and domestic duties.…”
Section: Is Fathers' Take-up Of Leave Associated With An Equal Divisi...mentioning
confidence: 99%
“…Leave takeup was measured with a four-category ordinal variable determined in accordance with the Finnish leave scheme (see section on Finnish context): no leave (reference category), 1-3 weeks of leave (an amount corresponding to the paternity leave that fathers can take at the same time as the mother, usually at childbirth), 4-9 weeks of leave (an amount corresponding to leave that, on top of the previously mentioned leave, also includes the individual leave quota for fathers) and three months or more of leave (which would include, on top of the leave ear-marked for fathers, either parental leave or childcare leave to be shared according to the parents' wishes). 4 These categories were also used because previous research has shown that father's individual leave for periods longer than just one or two weeks is of critical importance for the division of care responsibilities between parents (Almqvist & Duvander, 2014;Bünning 2015;Everttson et al 2018;Hosking et al 2010;Miller 2011;Reimer & Pfau-Effinger 2020).…”
Section: Variablesmentioning
confidence: 99%